Réponses

2014-02-16T15:33:41+01:00
A =13/12-3/2 x 1/3 = 13/12 - 3/6 = 13/12 - 6/12 =7/12

b = 8 - 5 x 3/7 = 8 - 15/7 = 56/7-15/7= 41/7
c = 2/9+7/9 x 11/2 = 2/9 + 88/18 = 4/18+88/18 = 92/18 =46/9

d = 11/12 x 4 -4 x 2/3 = 44/12 -8/3 =11/3-8/3 = 3/3 =1
merci beaucoup
nonotata je pense que tu t'es trompé pour la c), 7x11 = 77
merci !
Le commentaire a été supprimé
Meilleure réponse !
2014-02-16T15:42:48+01:00
A) 13/12 - 3/2 x 1/3
= 13/12 - 3/6
= 13/12 - (3x2) / (6x2)
= 13/12 - 6/12
7/12

b) 8 - 5 x 3/7
= 8/1 - 15/7
= (8x7) / (1x7) - 15/7
= 56/7 - 15/7
= 41/7

c) 2/9 + 7/9 x 11/2
= 2/9 + 77/18
= (2x2)/(9x2) + 77/18
= 4/18 + 77/18
= 81/18

d) 11/12 x 4 - 4 x 2/3
= 44/12 - 8/3
= 44/12 - (8x4) / (3x4)
= 44/12 - 32/12
= 12/12
= 1